The Macroeconomic Effects of Reserve Requirements - Christian Glocker; Pascal Towbin (Austrian Institute of Economic Research (WIFO), 2012)
When dealing with credit booms driven by capital inflows, monetary authorities in emerging markets are often reluctant to raise interest rates, as they fear that an increase attracts even more capital and appreciates the currency. A number of countries therefore use reserve requirements as an additional policy instrument. The present study provides evidence on their macroeconomic effects. We estimate a vector autoregressive (VAR) model for the Brazilian economy and identify interest rate and reserve requirement shocks. For both instruments a discretionary tightening leads to a decline in domestic credit. We find, however, very different effects for other macroeconomic aggregates. In contrast to interest rate policy, a positive reserve requirement shock leads to an exchange rate depreciation and an improvement in the current account, but also to an increase in prices. The results suggest that reserve requirement policy can complement interest rate policy in pursuing a financial stability objective, but cannot be its substitute with regards to a price stability objective.
Keywords: 330; Reserve Requirements; Capital Flows; Monetary Policy; Business Cycle; Mindestreserve; Wirkungsanalyse; Wirkungsanalyse; Kapitalimport; VAR-Modell; Schätzung; Brasilien